The dynamic interaction between monetary and fiscal policies in Indonesia - Haryo Kuncoro; K. Dianta A. Sebayang (Romanian Journal of Fiscal Policy (RJFP), 2013)
The aim of this paper is to analyze the dynamic interaction between monetary and fiscal policies in Indonesia for the period of 1999 - 2010. First, we propose the reaction function between monetary and fiscal policies. Second, we identify the main determinants of both interaction decisions, i.e. interest rate and primary balance surplus. The results of quarterly data estimation show that in the short term monetary policy reacts as expected to the fiscal policy - in the sense that governments have the ability to run a primary surplus. This action makes fiscal sustainability easier to achieve in the long run. On the other hand, fiscal policy marginally reacts to the monetary policy (interest rate) so that fiscal sustainability will be more difficult to attain given the opposite response of governments to public debt shocks. Furthermore, the interaction matrix indicates that monetary policy is more dominant in Indonesia. In these circumstances, the active fiscal policy should be made in order to reach economic growth sustainability in the long run.
Keywords: E58; E62; E63; 330; Monetary Policy; Fiscal Policy; Interest Rates; Primary Surplus